Management of Hereditary Spastic Paraplegia: A Systematic Review of the Literature - Bellofatto, Marta; De Michele, Giovanna; Iovino, Aniello; Filla, Alessandro; Santorelli, Filippo M. (Frontiers in Neurology, 2019)
The term hereditary spastic paraplegia (HSP) embraces a clinically and genetically heterogeneous group of neurodegenerative diseases characterized by progressive spasticity and weakness of the lower limbs. There currently exist no specific therapies for HSP, and treatment is exclusively symptomatic, aimed at reducing muscle spasticity and improving strength and gait. The authors set out to perform a comprehensive systematic review of the available scientific literature on the treatment of HSP, applying Cochrane Collaboration methods. The Google Scholar, PubMed and Scopus electronic databases were searched to find relevant randomized control trials (RCTs) and open-label interventional studies, prospective and retrospective observational studies of supplements, medications and physical therapy, as well as case reports and case series. Two authors independently analyzed 27 articles selected on the basis of a series of inclusion criteria. Applying a best-evidence synthesis approach, they evaluated these articles for methodological quality. A standardized scoring system was used to obtain interrater assessments. Disagreements were resolved by discussion. The 27 articles focused on pharmacological treatment (n=17 articles), physical therapy (n=5), surgical treatment (n=5). The drugs used in the 17 articles on pharmacological therapy were: gabapentin, progabide, dalfampridine, botulinum toxin, L-Dopa, cholesterol-lowering drugs, betaine and folinic acid. Gabapentin, progabide, dalfampridine, and botulinum toxin were used as antispastic agents; the study evaluating gabapentin efficacy was well designed, but failed to demonstrate any significant improvement. L-Dopa, cholesterol-lowering drugs, betaine and folinic acid were only used in specific HSP subtypes. Two of the three studies evaluating cholesterol-lowering drugs (in SPG5 patients) were well designed and showed a significant reduction of specific serum biomarkers (oxysterols), but clinical outcomes were not evaluated. The articles focusing on physical treatment and surgical therapy were found to be of low/medium quality and, accordingly, failed to clarify the role of these approaches in HSP. Despite recent advances in understanding of the pathogenesis of HSP and the possibility, in several centers, of obtaining more precise and rapid molecular diagnoses, there is still no adequate evidence base for recommending the various published therapies. Well-designed RCTs are needed to evaluate the efficacy of both symptomatic and pathogenetic treatments.